A distributed particle filtering approach for multiple acoustic source tracking using an acoustic vector sensor network - Zhong, Xionghu; Mohammadi, Arash; Premkumar, A.B.; Asif, Amir (Signal processing, 2015)
Different centralized approaches such as least-squares (LS) and particle filtering (PF) algorithms have been developed to localize an acoustic source by using a distributed acoustic vector sensor (AVS) array. However, such algorithms are either not applicable for multiple sources or rely heavily on sensor-processor communication. In this paper, a distributed unscented PF (DUPF) approach is proposed for multiple acoustic source tracking. At each distributed AVS node, the first-order and the second-order statistics of the local state are estimated by using an unscented information filter (UIF) based PF. The UIF is employed to approximate the optimum importance function due to its simplicity, by which the matrix operation is the state information matrix rather than the covariance matrix of the measurement sequence. These local statistics are then fused between neighbor nodes and a consensus filter is applied to achieve a global estimation. In such an architecture, only the state statistics need to be transmitted among the neighbor nodes. Consequently, the communication cost can be reduced. The distributed posterior Cramér–Rao bound is also derived. Simulation results show that the performance of the DUPF tracking approach is similar to that of centralized PF algorithm and significantly better than that of LS algorithms. •Multiple wideband source tracking using a distributed AVS network is considered.•A distributed PF approach is developed to track multiple sources in 3-D space.•The theoretical performance bound (posterior Cramer-Rao lower bound) is derived.•Simulations are organized to demonstrate the performance of the proposed approach.